Trobar sabor, trovar selvagem: contra-história do poema de amor - Otávio Augusto de Oliveira Moraes (2023)
The present thesis, using an essay structure, proposes a mythological reading of the discourse of love. Myth is thought through the conceptual proposals elaborated by Claude Lévi-Strauss and Roland Barthes. The text, anchored in Galician-Portuguese troubadourism, investigates the meanings of the discourse of love, taking its variations as an indication of continuity. In this sense, the thesis is a kind of counterhistory of Literature. Instead of focusing its efforts on the elaboration of a genealogy of love discourse, the thesis makes contemporary Brazilian poetry and its love songs the privileged interlocutors of the past. From such an exercise emerges a critical production of a kaleidoscopic nature. Trovadorism and its imaginary love are no longer instituted as foundational landmarks within a linear perspective of literary historiography. In the reversal of such a perspective, the thesis proposes multiple destinations for the love discourse, therefore, a game of aesthetic-historical coherence in which paths necessarily fork.